(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2025)
This article explores the stages of physical development in athletes, beginning from early youth and progressing to the professional level. It discusses physiological changes, training adaptations, and the impact of age-appropriate conditioning. Emphasis is placed on the importance of long-term athletic development (LTAD), injury prevention, and the role of specialized training in maximizing athletic performance at each stage of growth.